The issue of Bessarabia in Ukrainian-Romanian relations at 1917–1918 - Пономарьов О. (Київський національний університет імені Тараса Шевченка, 2007)
The article deals with the ukrainian-romanian relations of 1917–1918, the reasons for rising of Bessarabian problem, historiography of the issue in the whole.

Розглянуто українсько-румунські відносини 1917–1918 рр., причини виникнення бессарабської проблеми, історіографія питання в цілому.
Бессарабське питання в українсько-румунських відносинах у 1917–1918 роках